Kedudukan Ahli Waris yang Tidak Mau Menyelesaikan Hutang Pewaris dan Pembagian Harta Warisnya - Naura Nurul Fajri (AHKAM, 2025)
Cases involving the refusal of inheritance by heirs often give rise to legal complications, particularly when the decedent dies under unnatural circumstances—such as homicide—and the order of death is uncertain. In such situations, heirs may reject the inheritance to avoid assuming the deceased’s outstanding debts. However, Islamic law upholds the ijbari principle, which mandates the acceptance of inheritance as a divine decree, determining both the share and the rightful recipients. This study aims to examine the legal mechanism for refusing inheritance and the distribution procedure when the primary heirs are no longer available. A quantitative method with a normative juridical approach was employed, utilizing primary data from statutory regulations, academic literature, and previous studies, alongside secondary data derived from publicly reported case chronologies in online media. The findings reveal that the refusal of inheritance (takharruj) is legally valid only if submitted directly by the concerned heir before a court and cannot be represented by third-party declarations. Furthermore, the distribution of the estate must proceed in accordance with the rights of lawful heirs or eligible substitutes. The study concludes that, under both Islamic and civil law, inheritance refusal is permissible, provided that it follows formal legal procedures. The implication is that any form of inheritance refusal must be formally submitted by the rightful heir in court to attain legal validity and to prevent potential disputes.